Message from The Heart?: An exploratory study on songs / Ching Lai Hock - Ching, Lai Hock (1985)
As suggested by the title, the objective of this study is to determine whether songs project the values and attitudes of their fans. In order to achieve this objective, this study will first try to determine if all songs are popular because of their lyrics. If not, what type of songs, based on their lyrical content are. After identifying the songs which are meaningful to their fans this study tries to identify the values and concepts described by those songs. From here, we can compare the ‘picture’ as described by those songs with existing known concepts about a subject. Therefore, this study being exploratory is basically an attempt to gather evidence to substantiate present general opinion about the role of song and its components.